Impact of Transverse Mode Resonances on Second Harmonic Generation in Radio-frequency Bulk Acoustic Wave Resonators. (10th June 2019) - Qiu, Luyan; Li, Xinyi; Matsuoka, Naoto; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: This paper investigates the impact of transverse mode resonances on second harmonic (H2) generation in radio-frequency bulk acoustic wave devices. Previous work indicated that second-order nonlinearity of the main mode can be well simulated by one-dimensional perturbation analysis using the h -form piezoelectric constitutive equations. This work expands the analysis to the two-dimensional case to investigate the influence of transverse resonances on the H2 generation. The result shows that transverse modes generate strong H2 responses, and this phenomenon is consistent with experimental results. The origin of the strong H2 generation is also discussed.